The Use of Think-Talk-Write Strategy To Improve Students Writing Ability - Nurjanna; Nasrullah A (La Parole : Journal of Language Teaching and Pedagogy, 2018)
Writing is one of language skill that used to give information to people besides speaking. In writing, the students need ideas to share information to make the good sentences or paragraph as the final product. Writing is considering as one of difficult for students, because in writing skill, the students have to master vocabulary and know how to use grammar in making texts or sentences. Those become the considerations of the researcher when doing an observation at SMP Negeri 12 Parepare. Then modifying a collaborative learning strategy can become a problem solving in writing. In this case, the implementation of Think-Talk-Write Strategy as a collaborative learning is suggested overcame the problem.The objective of the research is to find out whether or not The Use of Think-Talk-Write (TTW) Strategy to Improve Writing Ability on Descriptive Text of Eight Year Students at SMP Negeri 12 Parepare. The researcher applied quasiexperimental method applied two group pre-test and post test design. One class was taken as an experimental class and one class as control class. The samples of the research consisted of 48 students from two classes taken from the population of the eighth year students of SMP Negeri 12 Parepare. The result of the data analysis showed that the students writing ability increase significantly. It could be showed from the mean score of pre-test was 49.04 and the post-test was 84 It could be concluded that the use of TTW strategy can increase the writing ability of SMP Negeri 12 Parepare. Therefore, the researcher also analyzed the data by using the test formula. The result of t-test value in the post-test was 6.27 and the t-table value was 2.021. It meant that the t-test value was higher than t-table value. Those indicated that H0 was rejected and H1 was accepted. It meant that there is significance between the students writing skill of eight year students of SMP Negeri 12 Parepare who are taught trought TTW Strategy and who are thaught trought Expository Strategy.